Fate of trace elements and emerging environmental pollutants (benzotriazoles and benzothiazoles) from a glacier-fed river in the mixing zone of an Arctic fjord system - Joséphine Amey; Øyvind Mikkelsen (Environmental Chemistry and Ecotoxicology)
The fate of organic and inorganic pollutants was studied in the Arctic, in the mixing zone of freshwater and seawater of a glacier-fed river and a fjord (Ny-Ålesund, Svalbard). Concentrations of trace elements and contaminants of emerging concern, benzotriazoles and benzothiazoles (BTRs and BTHs), were assessed. Metal concentrations of Al, As, Cr, Hg, Mo, Ni, Pb, Sb, Sn, V, and Zn in marine sediment were up to two or three times higher than in riverine sediment and most of them showed an increasing trend from the upper to the lower part of the river. Pb (0.058 μg/L) and Zn (0.80 μg/L) were present in levels of moderate pollution in seawater close to town, while Cu (0.11 μg/L) exceeded background levels in the same area. As (0.042 μg/L), Hg (0.004 μg/L) and Cd (0.011 μg/L) showed levels of low to moderate pollution in freshwater from the river. In seawater and river water detected BTRs and BTHs were: BTR, TTR, 2-OH-BTH, XTR, 2-Me-S-BTH, 2-M-BTH, 2-S-BTH, and 2-NH2-BTH. Considerably high concentrations of BTR (1460 ng/L) and 2-OH-BTH (1070 ng/L) were found. Compounds present in marine and riverine sediment were BTR, 2-OH-BTH, 2-Me-S-BTH, and 2-M-BTH. Sediment appeared to be a significant sink of BTRs and BTHs with a concentration range of 1.13–32.7 ng/g. A trend of higher concentrations of trace elements in sediment (ANOVA, p = 0.044) and seawater (ANOVA, p = 0.013), as well as 2-OH-BTH in seawater (t-test, p = 0.010) was observed in the vicinity of the town, where most anthropogenic activities have taken place due to former mining operations.